2006
DOI: 10.2109/jcersj.114.1
|View full text |Cite
|
Sign up to set email alerts
|

The Electrophoretic Deposition of Inorganic Nanoscaled Materials-A Review-

Abstract: Electrophoretic deposition EPD is gaining increasing interest as a processing technique for production of novel inorganic nanostructured and nanoscale materials, including the use of nanoparticles, nanotubes, nanorods and related nanomaterials. Recent advances in the electrophoretic deposition of a great variety of ceramic and metallic nanoparticles, carbon nanotubes and other inorganic nanoscaled materials are discussed in this review. The purpose of the paper is to demonstrate the utility of an applied elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
78
0
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 137 publications
(92 citation statements)
references
References 156 publications
(138 reference statements)
0
78
0
3
Order By: Relevance
“…Moreover, it can be used both on a large scale, also when coating objects with a complex geometrical form, and on a small scale, to fabricate composite microand nanostructures. New application areas for EPD are the low-cost fabrication of composite Formation of Nanolayer on Surface of EPD Coatings Based on Poly-Ether-Ether-Ketone http://dx.doi.org/10.5772/67570 5 materials including advanced coatings based on nanocomposites, laminate structures and functional graded materials [10][11][12][13].…”
Section: Deposition Processmentioning
confidence: 99%
“…Moreover, it can be used both on a large scale, also when coating objects with a complex geometrical form, and on a small scale, to fabricate composite microand nanostructures. New application areas for EPD are the low-cost fabrication of composite Formation of Nanolayer on Surface of EPD Coatings Based on Poly-Ether-Ether-Ketone http://dx.doi.org/10.5772/67570 5 materials including advanced coatings based on nanocomposites, laminate structures and functional graded materials [10][11][12][13].…”
Section: Deposition Processmentioning
confidence: 99%
“…[15,16] EPD consists of the movement of charged particles suspended in liquid and deposition onto a conducting substrate under the influence of an externally applied electrical field. [17,18] The advantages of this method are high purity, easy control of the coating thickness, high coating uniformity, the possibility of using complex shaped substrates, and the short deposition time of coatings. [19,20] One of the popular materials with useful properties for a relatively strong porous coating matrix is polyetheretherketone (PEEK).…”
Section: Introductionmentioning
confidence: 99%
“…A numbers of reviews reported extensively on the several applications of EPD as coatings and free standing objects, based on ceramics and metals (Sarkar & Nicholson, 1996;Van der Biest & Vandeperre, 1999;Boccaccini & Zhitomirsky, 2002;Boccaccini et al, 2003;Besra & Liu, 2007;Corni et al, 2008). Particularly successful is the use of EPD to produce porous, laminated and graded ceramic coatings (Hatton & Nicholson, 2001;Put et al, 2004;You et al, 2004) as well as fibres reinforced composites (Boccaccini et al, 1996(Boccaccini et al, ,1997Wang et al, 2000a;Freidrich et al, 2002;Kaya et al, 1999Kaya et al, , 2000Kaya et al, , 2001.…”
Section: Applications: From Traditional To Advanced Materialsmentioning
confidence: 99%